2007 2nd IEEE International Conference on Nano/Micro Engineered and Molecular Systems 2007
DOI: 10.1109/nems.2007.352171
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Continuous Blood Cell Subtype Separation by Deterministic Lateral Displacement

Abstract: This paper presents a microfluidic device for continuous human blood cell subtype separation using the deterministic lateral displacement principle. Based on their significant size and shape differences, three major cell types of human whole blood -platelets, red blood cells and white blood cells -were demonstrated to be directly separated using a twostage separation strategy. Even though all white blood cells are spherical and have diameters within a narrow range (8 -20pm), the initial limitation for using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…More recently, it has been shown that DLD can also fractionate samples based on shape and deformability (Quek et al 2011;Bogunovic et al 2012;Beech et al 2012;Zeming et al 2013;Ranjan et al 2014;Krüger et al 2014;Holmes et al 2014). DLD has been successful in the fractionation of various mixtures, including biological samples and cells in particular (Beech et al 2012;Zeming et al 2013;Ranjan et al 2014;Krüger et al 2014;Holmes et al 2014;Siyang Zheng et al 2005;Davis et al 2006;Nan Li et al 2007;Huang et al 2008;Inglis et al 2008;Morton et al 2008;Green et al 2009;Inglis et al 2010;Holm et al 2011;Al-Fandi et al 2011;Inglis et al 2011;Zhang et al 2012;Loutherback et al 2012;Liu et al 2013;Ozkumur et al 2013;Karabacak et al 2014), which makes it attractive for lab-on-a-CD applications. In addition, different post geometries (Loutherback et al 2010;Al-Fandi et al 2011;Ranjan et al 2014) and other design considerations (Inglis 2009) have been proposed to improve performance.…”
Section: Deterministic Lateral Displacement Separation Systemsmentioning
confidence: 99%
“…More recently, it has been shown that DLD can also fractionate samples based on shape and deformability (Quek et al 2011;Bogunovic et al 2012;Beech et al 2012;Zeming et al 2013;Ranjan et al 2014;Krüger et al 2014;Holmes et al 2014). DLD has been successful in the fractionation of various mixtures, including biological samples and cells in particular (Beech et al 2012;Zeming et al 2013;Ranjan et al 2014;Krüger et al 2014;Holmes et al 2014;Siyang Zheng et al 2005;Davis et al 2006;Nan Li et al 2007;Huang et al 2008;Inglis et al 2008;Morton et al 2008;Green et al 2009;Inglis et al 2010;Holm et al 2011;Al-Fandi et al 2011;Inglis et al 2011;Zhang et al 2012;Loutherback et al 2012;Liu et al 2013;Ozkumur et al 2013;Karabacak et al 2014), which makes it attractive for lab-on-a-CD applications. In addition, different post geometries (Loutherback et al 2010;Al-Fandi et al 2011;Ranjan et al 2014) and other design considerations (Inglis 2009) have been proposed to improve performance.…”
Section: Deterministic Lateral Displacement Separation Systemsmentioning
confidence: 99%
“…This principle was applied to separate RBCs, WBCs, and platelets (Davis et al, 2006; Zheng et al, 2005a; Zheng et al, 2005b). More recently a subpopulation (CD4 + T helper lymphocytes) of WBCs was successfully fractionated by increasing the hydrodynamic radius through affinity binding of antibody-coated microbeads (Li et al, 2007). …”
Section: Passive Separation Based On Microstructures and Laminar Flowmentioning
confidence: 99%
“…Strong, nonuniform and time varying electric fields can be generated on-chip without the need for applying high external potentials. It has been demonstrated in various applications, that DEP is suitable to separate different types of mammalian cells (Yang et al, 2000(Yang et al, , 1999bGiddings, 1993;Rousselet et al, 1998;Kersaudy-Kerhoas et al, 2008;Huang et al, 1999), yeast (Doh et al, 2004;Li et al, 2007), bacteria (Lapizco-Encinas et al, 2004;Hu et al, 2005) or polymeric particles (Rousselet et al, 1998;Kralj et al, 2006) into different fluid streams, which allows continuous or batch fractionation. DEP has been also successfully used for cell guiding and trapping (Muller et al, 1999;Voldman et al, 2002), which could be used for medium removal and cell washing.…”
Section: Dielectrophoretic Separationmentioning
confidence: 99%